Two new RC oscillators using CCIIs - Fongsamut, Chalermpan; Fujii, Nobuo; Surakampontorn, Wanlop (My University, 2005)
Two new sinusoidal oscillator circuits using current conveyors are presented in this paper. The two oscillators are related to each other by the RC:CR transformation. Each oscillator consists of two positive second-generation current conveyors (CCII+) and the minimum of (four) passive elements, two capacitors and two resistors. One of the oscillators can be realized by employing grounded capacitors and is desirable for VLSI realization. The passive and active sensitivities of all circuits are quite low. The SPICE simulation and experimental works are performed to verify this theoretical prediction. © 2005 IEEE.
Keywords: Oscillators; Second Generation Current Conveyors and Grounded Capacitor; Voltage-Control-Oscillators